High-strain-performance sodium bismuth titanate-strontium titanate-lead titanate ternary ceramic material obtained through bismuth reduction and preparation method of high-strain-performance sodium bismuth titanate-strontium titanate-lead titanate ternary ceramic material

The ternary ceramic material of sodium bismuth titanate-strontium titanate-lead titanate prepared by bismuth reduction reaction solves the problem of unstable electrostrain performance of existing ceramic materials under low electric field, and achieves a larger size under low electric field The electro-strain and electro-memory effects are suitable for the piezoelectric driving field.

CN119161183AActive Publication Date: 2024-12-20HARBIN INST OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411278164.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-20
Estimated Expiration
2044-09-12

AI Technical Summary

Technical Problem

Existing electromemory effect ceramic materials exhibit unstable high electrostrain properties at low electric fields, require large electric field drives, and lack the ability to maintain deformation under either the removal of electric fields or the low electric fields.

Method used

The ternary ceramic material of sodium bismuth titanate-strontium titanate-lead titanate prepared by bismuth reduction reaction was obtained by initiating strong and weak reduction reactions of bismuth elements under the electric field, and a large electro-strain and electro-strain memory effect was obtained. . The material is prepared by mixing Na2CO3, SrCO3, TiO2, Bi2O3 and PbO in a stoichiometric ratio, and is prepared by ball milling, pre-sintering, granulation, sintering and electric field pretreatment.

Benefits of technology

Stable large electrostrain and electrostrain memory effects are achieved under a lower electric field. The material is simple to prepare and the cost is low. The maximum strain reaches 2.77%, and the strain memory effect is 1.75%, which is suitable for the piezoelectric driving field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119161183A_ABST
    Figure CN119161183A_ABST
Patent Text Reader

Abstract

The invention discloses a high-strain-performance sodium bismuth titanate-strontium titanate-lead titanate ternary ceramic material obtained by bismuth reduction and a preparation method thereof, and aims to solve the problems that defect-modified sodium bismuth titanate ceramic is unstable in performance and needs to be driven by a large electric field and the like. The chemical general formula of the sodium bismuth titanate-strontium titanate-lead titanate ternary ceramic material is (Na < 0.5 > Bi < 0.5 >) < 0.75 > (1-x) Sr < 0.25 > (1-x) Pb < x > TiO < 3 >, and the sodium bismuth titanate-strontium titanate-lead titanate ternary ceramic material is prepared by mixing Na2CO3, SrCO3, TiO2, Bi2O3 and PbO according to the stoichiometric ratio of (Na < 0.5 > Bi < 0.5 >) < 0.75 > (1-x) Sr < 0.25 > (1-x) Pb < x > TiO < 3 > and then pressing and sintering. The maximum strain of the sodium bismuth titanate-strontium titanate-lead titanate ternary ceramic under an electric field of 80kV / cm is 2.77%, and the strain memory effect is 1.75%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of piezoelectric ceramics, and specifically relates to a sodium bismuth titanate-strontium titanate-lead titanate ceramic material that utilizes bismuth element reduction to obtain high strain performance and a preparation method thereof, and is used as a driving material with large electro-induced strain and large strain memory effect. Background Art

[0002] Piezoelectric ceramics are a type of electronic ceramics with good electromechanical conversion performance and are widely used in sensors, drives and other fields. Piezoelectric ceramics can undergo a certain deformation under the action of an external electric field. This deformation generally does not have a memory effect, and the deformation disappears when the external electric field is removed. However, in some scenarios, piezoelectric actuators need to maintain a certain deformation (electro-induced shape memory effect, SME) when the electric field is removed or the electric field is low, such as ferroelectric random access memory technology, mechanical relays, etc. Therefore, it is of great significance to develop piezoelectric ceramics with good electro-induced shape memory effect.

[0003] The electromechanical memory effect ceramics that have been discovered so far are mainly realized by designing antiferroelectric-ferroelectric phase transition and defect modification. Doped modified lead zirconate titanate ceramics, lead zirconate titanate single crystals; sodium bismuth titanate ceramics, bismuth ferrite ceramics and bismuth tungstate ceramics with textured structures modified by defects, etc. These ceramic materials generally require large electric fields to drive, and the high electromechanical strain performance induced by defects is unstable. Therefore, designing a piezoelectric ceramic with low-field operation, stable large electromechanical response and memory effect is an important technical problem that needs to be solved urgently. Summary of the invention

[0004] The purpose of the present invention is to solve the problems of unstable performance and large electric field driving of defect-modified sodium bismuth titanate ceramics, and to provide a sodium bismuth titanate-strontium titanate-lead titanate ternary ceramic material with high strain performance obtained by bismuth reduction and a preparation method thereof.

[0005] The chemical composition formula of the sodium bismuth titanate-strontium titanate-lead titanate ternary ceramic material with high strain performance obtained by bismuth reduction is (Na 0.5 Bi 0.5 ) 0.75(1-x) Sr 0.25(1-x) Pb x TiO3, wherein x = 0.05 to 0.4; the sodium bismuth titanate-strontium titanate-lead titanate ternary ceramic material is composed of Na2CO3, SrCO3, TiO2, Bi2O3 and PbO in a stoichiometric ratio of (Na 0.5 Bi 0.5 ) 0.75(1-x) Sr 0.25(1-x) Pb x TiO3 is mixed and then pressed and sintered.

[0006] The preparation method of the sodium bismuth titanate-strontium titanate-lead titanate ternary ceramic material with high strain performance obtained by bismuth reduction of the present invention is achieved by the following steps:

[0007] 1. Ingredients:

[0008] According to the stoichiometric ratio (Na 0.5 Bi 0.5 ) 0.75(1-x) Sr 0.25(1-x) Pb x TiO3 weighed Na2CO3, SrCO3, TiO2, Bi2O3 and PbO as raw materials;

[0009] 2. Ball milling:

[0010] The raw materials in step 1 are placed in a ball mill for ball milling, and then dried to obtain a mixed powder;

[0011] 3. Pre-burning:

[0012] Pre-sintering the mixed powder at a temperature of 850-950° C. to obtain a pre-sintered powder;

[0013] 4. Secondary ball milling:

[0014] The pre-sintered powder is put into the ball mill again for secondary ball milling, and then dried to obtain the ball milled mixed powder;

[0015] 5. Granulation:

[0016] The ball-milled mixed powder is ground and sieved, and then a binder is added and fully ground to granulate to obtain a granulated powder;

[0017] 6. Molding:

[0018] Put the granulated powder into a mold and press it into flakes;

[0019] 7. Debinding:

[0020] Using a sintering furnace to heat treat the sheet material at a temperature of 500 to 600° C. to remove binder, thereby obtaining a debinded ceramic sheet;

[0021] 8. Sintering:

[0022] The debinded ceramic sheet is sintered at a temperature of 1130-1150° C. to obtain a ternary ceramic material;

[0023] 9. Electrode plating:

[0024] Polishing both sides of the ternary ceramic material, then evenly brushing conductive silver paste on both sides of the ceramic, drying and annealing at 500-600°C to obtain a ceramic sheet with silver electrodes;

[0025] 10. Electric field pretreatment:

[0026] The ceramic sheet with silver electrodes is placed in a 40-70 kV / cm electric field for polarization treatment, so that part of the bismuth element in the ceramic undergoes a reduction reaction, thereby obtaining a sodium bismuth titanate-strontium titanate-lead titanate ternary ceramic material with high strain performance.

[0027] The present invention proposes a sodium bismuth titanate-strontium titanate-lead titanate ternary ceramic, which utilizes the fact that the bismuth element in the ceramic undergoes a strong reduction reaction on one side under an electric field and a weak reduction reaction on the other side, thereby obtaining a large electro-induced strain and electro-induced strain memory effect. The application of the sodium bismuth titanate-strontium titanate-lead titanate ternary ceramic material that obtains high strain performance by bismuth reduction described in the present invention is to use the sodium bismuth titanate-strontium titanate-lead titanate ternary ceramic material as a driving material.

[0028] The sodium bismuth titanate-strontium titanate-lead titanate ternary ceramic (Na 0.5 Bi 0.5 ) 0.75(1-x) Sr 0.25(1-x) Pb x The maximum strain of TiO3 (x = 0.4) under 80kV / cm electric field is 2.77%, and the strain memory effect is 1.75%. The preparation process of this ternary system is simple and easy to operate, the required material cost is low, and a large electro-induced strain and memory effect can be obtained, which is of great significance in the field of piezoelectric drive. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Given the conditions of this example (Na 0.5 Bi 0.5 ) 0.75(1-x) Sr 0.25(1-x) Pb x XRD patterns of TiO3 (x = 0.05, 0.1, 0.2, 0.4) ceramics;

[0030] Figure 2 Given the conditions of this example (Na 0.5 Bi 0.5 ) 0.75(1-x) Sr 0.25(1-x) Pb x Strain curves of TiO3 (x = 0.05, 0.1, 0.2, 0.4) ceramics at the same frequency (10 Hz) 60 kV / cm;

[0031] Figure 3 Given the conditions of this example (Na 0.5 Bi 0.5 ) 0.75(1-x) Sr 0.25(1-x) Pb xTest diagram of maximum strain and strain memory effect of TiO3 (x=0.05, 0.1, 0.2, 0.4) ceramics at different frequencies. DETAILED DESCRIPTION

[0032] Specific implementation method 1: In this implementation method, the chemical composition formula of the sodium bismuth titanate-strontium titanate-lead titanate ternary ceramic material with high strain performance obtained by bismuth reduction is (Na 0.5 Bi 0.5 ) 0.75(1-x) Sr 0.25(1-x) Pb x TiO3, wherein x = 0.05 to 0.4; the sodium bismuth titanate-strontium titanate-lead titanate ternary ceramic material is composed of Na2CO3, SrCO3, TiO2, Bi2O3 and PbO in a stoichiometric ratio of (Na 0.5 Bi 0.5 ) 0.75(1-x) Sr 0.25(1-x) Pb x TiO3 is mixed and then pressed and sintered.

[0033] Specific embodiment 2: This embodiment is different from the specific embodiment 1 in that the chemical composition formula (Na 0.5 Bi 0.5 ) 0.75(1-x) Sr 0.25(1-x) Pb x In TiO3, x=0.2~0.4.

[0034] In the chemical formula of the ternary ceramic material of the present embodiment, x is preferably 0.2 to 0.4.

[0035] Specific implementation method three: In this implementation method, the preparation method of sodium bismuth titanate-based ceramics with high strain performance by using asymmetric polarization-induced ceramic bending deformation is implemented according to the following steps:

[0036] 1. Ingredients:

[0037] According to the stoichiometric ratio (Na 0.5 Bi 0.5 ) 0.75(1-x) Sr 0.25(1-x) Pb x TiO3 weighed Na2CO3, SrCO3, TiO2, Bi2O3 and PbO as raw materials;

[0038] 2. Ball milling:

[0039] The raw materials in step 1 are placed in a ball mill for ball milling, and then dried to obtain a mixed powder;

[0040] 3. Pre-burning:

[0041] Pre-sintering the mixed powder at a temperature of 850-950° C. to obtain a pre-sintered powder;

[0042] 4. Secondary ball milling:

[0043] The pre-sintered powder is put into the ball mill again for secondary ball milling, and then dried to obtain the ball milled mixed powder;

[0044] 5. Granulation:

[0045] The ball-milled mixed powder is ground and sieved, and then a binder is added and fully ground to granulate to obtain a granulated powder;

[0046] 6. Molding:

[0047] Put the granulated powder into a mold and press it into flakes;

[0048] 7. Debinding:

[0049] Using a sintering furnace to heat treat the sheet material at a temperature of 500 to 600° C. to remove binder, thereby obtaining a debinded ceramic sheet;

[0050] 8. Sintering:

[0051] The debinded ceramic sheet is sintered at a temperature of 1130-1150° C. to obtain a ternary ceramic material;

[0052] 9. Electrode plating:

[0053] Polishing both sides of the ternary ceramic material, then evenly brushing conductive silver paste on both sides of the ceramic, drying and annealing at 500-600°C to obtain a ceramic sheet with silver electrodes;

[0054] 10. Electric field pretreatment:

[0055] The ceramic sheet with silver electrodes is placed in a 40-70 kV / cm electric field for polarization treatment, so that part of the bismuth element in the ceramic undergoes a reduction reaction, thereby obtaining a sodium bismuth titanate-strontium titanate-lead titanate ternary ceramic material with high strain performance.

[0056] In order to obtain a large electrostrain under a relatively low electric field, this embodiment utilizes the reduction reaction of the bismuth element to stabilize the polarization effect, thereby obtaining a large electrostrain and an electrostrain memory effect.

[0057] Specific implementation method 4: This implementation method is different from specific implementation method 3 in that the ball milling treatment in step 2 is carried out at a rotation speed of 200 r / min for 10 to 12 hours.

[0058] Specific implementation method five: This implementation method is different from specific implementation methods three or four in that the pre-firing treatment time in step three is 2 to 6 hours.

[0059] Specific implementation example 6: This implementation example is different from any one of specific implementation examples 3 to 5 in that the binder described in step 5 is 5 wt.% polyvinyl alcohol (PVA).

[0060] Specific implementation method seven: This implementation method is different from any one of specific implementation methods three to six in that the heat treatment debinding time in step seven is 1 to 2 hours.

[0061] Specific implementation eight: This implementation is different from any one of specific implementations three to seven in that the sintering treatment time in step eight is 3 to 3.5 hours.

[0062] Specific implementation method 9: This implementation method is different from any one of specific implementation methods 3 to 8 in that the annealing treatment time in step 9 is 0.4 to 0.8 hours.

[0063] Specific implementation method ten: The difference between this implementation method and any one of specific implementation methods three to nine is that in step ten, the ceramic sheet with the silver electrode is placed in an electric field of 40 to 70 kV / cm for polarization treatment for 50 to 70 seconds.

[0064] Embodiment: The preparation method of sodium bismuth titanate-strontium titanate-lead titanate ternary ceramic material with high strain performance obtained by bismuth reduction in this embodiment is implemented according to the following steps:

[0065] 1. Ingredients:

[0066] According to the stoichiometric ratio (Na 0.5 Bi 0.5 ) 0.75(1-x) Sr 0.25(1-x) Pb x TiO3 weighed Na2CO3, SrCO3, TiO2, Bi2O3 and PbO as raw materials;

[0067] 2. Ball milling:

[0068] The raw materials of step 1 are placed in a ball mill for ball milling. The ball milling medium is anhydrous ethanol and zirconium oxide grinding balls. The ball milling conditions are: ball-to-material mass ratio is 5:1, the rotation speed is 200r / min, the ball milling time is 12h, and the slurry is dried at 80°C to obtain a mixed powder;

[0069] 3. Pre-burning:

[0070] The mixed powder is pre-sintered by heating the mixture to 900°C at a heating rate of 10°C / min and maintaining the temperature for 4 hours to obtain a pre-sintered powder;

[0071] 4. Secondary ball milling:

[0072] The pre-sintered powder was put into the ball mill again, and the ball milling medium was anhydrous ethanol and zirconium oxide grinding balls. The ball milling conditions were: the rotation speed was 200r / min, and the ball milling time was 12h. The ball milling was carried out for the second time, and the ball milled mixed powder was obtained after drying (80℃);

[0073] 5. Granulation:

[0074] The ball-milled mixed powder is ground and sieved, and then 5 wt.% of polyvinyl alcohol (PVA) binder is added and fully ground to granulate to obtain a granulated powder;

[0075] 6. Molding:

[0076] The granulated powder is placed in a mold and pressed into a sheet material with a diameter of 10 mm and a thickness of 0.5 mm at a pressure of 8 MPa;

[0077] 7. Debinding:

[0078] The sintering furnace is used to heat up to 600°C at a heating rate of 2°C / min, and the temperature is kept for 1 hour to perform heat treatment and debinding on the sheet material to obtain a debinded ceramic sheet;

[0079] 8. Sintering:

[0080] The temperature was raised to 1150°C at a heating rate of 10°C / min and kept at that temperature for 3 hours, and the ceramic sheet after debinding was sintered to obtain a ternary ceramic material;

[0081] 9. Electrode plating:

[0082] The two sides of the ternary ceramic material are polished, and then the conductive silver paste is evenly applied on the two sides, and then annealed at 500°C for 30 minutes after drying to obtain a ceramic sheet with silver electrodes;

[0083] 10. Electric field pretreatment

[0084] The ceramic sheet with the silver electrode was placed in a 60 kV / cm electric field for polarization treatment for 60 seconds, so that part of the bismuth element in the ceramic was reduced to obtain a sodium bismuth titanate-strontium titanate-lead titanate ternary ceramic material with high strain performance.

[0085] The (Na 0.5 Bi 0.5 ) 0.75(1-x) Sr 0.25(1-x) Pb x The maximum electrostrain of TiO3 (x=0.05, 0.1, 0.2, 0.4) ternary ceramic material at 80 kV / cm and 0.1 Hz is 2.77%, and the electrostrain shape memory effect is 1.77%.

[0086] Figure 1Given the conditions of this example (Na 0.5 Bi 0.5 ) 0.75(1-x) Sr 0.25(1-x) Pb x XRD patterns of TiO3 (x = 0.05, 0.1, 0.2, 0.4) ceramics. Figure 1 It can be seen that the prepared ceramic sample is a pure perovskite phase without any impurity phase. In addition, the diffraction peak of the (200) crystal plane is split, and when x = 0.05, 0.1, the peak intensity ratio is not 1:2, indicating that the phase structure of the ceramic is the coexistence of R and T phases; when x = 0.2, 0.4, the peak intensity ratio is 1:2, proving that it is T phase.

[0087] Figure 2 Given the conditions of this example (Na 0.5 Bi 0.5 ) 0.75(1-x) Sr 0.25(1-x) Pb x Strain curves of TiO3 (x = 0.05, 0.1, 0.2, 0.4) ceramics at the same frequency (10Hz) 60kV / cm. Figure 2 It can be seen that (Na 0.5 Bi 0.5 ) 0.75(1-x) Sr 0.25(1-x) Pb x The maximum strain of TiO3 (x=0.05, 0.1, 0.2, 0.4) ceramics at 60 kV / cm is 0.76%, and the strain memory effect is 0.67% (x=0.2).

[0088] Figure 3 Given the conditions of this example (Na 0.5 Bi 0.5 ) 0.75(1-x) Sr 0.25(1-x) Pb x The maximum strain and strain memory effect of TiO3 (x = 0.05, 0.1, 0.2, 0.4) ceramics at different frequencies, where the applied electric field is 50 kV / cm for x = 0.05, 0.1, 0.2, and 80 kV / cm for x = 0.4. When x = 0.4 and the frequency is 0.1 Hz, (Na 0.5 Bi 0.5 ) 0.45 Sr 0.15 Pb 0.4 The maximum strain value of TiO3 reaches 2.77%, and the strain memory effect is 1.75%.

Claims

1. A ternary ceramic material of sodium bismuth titanate-strontium titanate-lead titanate with high strain performance obtained by bismuth reduction, characterized in that The chemical composition formula of the sodium bismuth titanate-strontium titanate-lead titanate ternary ceramic material that uses bismuth reduction to obtain high strain performance is (Na 0.5 Bi 0.5 ) 0.75(1-x) Sr 0.25(1-x) Pb x TiO3, wherein x = 0.05 to 0.4; the sodium bismuth titanate-strontium titanate-lead titanate ternary ceramic material is composed of Na2CO3, SrCO3, TiO2, Bi2O3 and PbO in a stoichiometric ratio of (Na 0.5 Bi 0.5 ) 0.75(1-x) Sr 0.25(1-x) Pb x TiO3 is mixed and then pressed and sintered.

2. The sodium bismuth titanate-strontium titanate-lead titanate ternary ceramic material with high strain performance obtained by bismuth reduction according to claim 1, characterized in that Chemical composition formula (Na 0.5 Bi 0.5 ) 0.75(1-x) Sr 0.25(1-x) Pb x In TiO3, x=0.2~0.

4.

3. A method for preparing a sodium bismuth titanate-strontium titanate-lead titanate ternary ceramic material with high strain performance by bismuth reduction, characterized in that The preparation method is achieved by the following steps:

1. Ingredients: According to the stoichiometric ratio (Na 0.5 Bi 0.5 ) 0.75(1-x) Sr 0.25(1-x) Pb x TiO3 weighed Na2CO3, SrCO3, TiO2, Bi2O3 and PbO as raw materials; 2. Ball milling: The raw materials in step 1 are placed in a ball mill for ball milling, and then dried to obtain a mixed powder; 3. Pre-burning: Pre-sintering the mixed powder at a temperature of 850-950° C. to obtain a pre-sintered powder; 4. Secondary ball milling: The pre-sintered powder is put into the ball mill again for secondary ball milling, and then dried to obtain the ball milled mixed powder; 5. Granulation: The ball-milled mixed powder is ground and sieved, and then a binder is added and fully ground to granulate to obtain a granulated powder; 6. Molding: Put the granulated powder into a mold and press it into flakes; 7. Debinding: Using a sintering furnace to heat treat the sheet material at a temperature of 500 to 600° C. to remove binder, thereby obtaining a debinded ceramic sheet; 8. Sintering: The debinded ceramic sheet is sintered at a temperature of 1130-1150° C. to obtain a ternary ceramic material; 9. Electrode plating: Polishing both sides of the ternary ceramic material, then evenly brushing conductive silver paste on both sides of the ceramic, drying and annealing at 500-600°C to obtain a ceramic sheet with silver electrodes; 10. Electric field pretreatment: The ceramic sheet with the silver electrode is placed in a 40-70 kV / cm electric field for polarization treatment to obtain a sodium bismuth titanate-strontium titanate-lead titanate ternary ceramic material with high strain performance.

4. The method for preparing the sodium bismuth titanate-strontium titanate-lead titanate ternary ceramic material with high strain performance obtained by bismuth reduction according to claim 3, characterized in that In step 2, the ball milling treatment is carried out at a rotation speed of 200 r / min for 10 to 12 hours.

5. The method for preparing sodium bismuth titanate-strontium titanate-lead titanate ternary ceramic material with high strain performance obtained by bismuth reduction according to claim 3, characterized in that The pre-burning treatment time in step 3 is 2 to 6 hours.

6. The method for preparing sodium bismuth titanate-strontium titanate-lead titanate ternary ceramic material with high strain performance obtained by bismuth reduction according to claim 3, characterized in that The binder described in step five is 5 wt.% polyvinyl alcohol.

7. The method for preparing sodium bismuth titanate-strontium titanate-lead titanate ternary ceramic material with high strain performance obtained by bismuth reduction according to claim 3, characterized in that The heat treatment debinding time in step seven is 1 to 2 hours.

8. The method for preparing sodium bismuth titanate-strontium titanate-lead titanate ternary ceramic material with high strain performance obtained by bismuth reduction according to claim 3, characterized in that The sintering treatment time in step eight is 3 to 3.5 hours.

9. The method for preparing sodium bismuth titanate-strontium titanate-lead titanate ternary ceramic material with high strain performance obtained by bismuth reduction according to claim 3, characterized in that The annealing treatment time in step nine is 0.4 to 0.8 h.

10. The method for preparing sodium bismuth titanate-strontium titanate-lead titanate ternary ceramic material with high strain performance obtained by bismuth reduction according to claim 3, characterized in that Step 10: Place the ceramic sheet with the silver electrode in a 40-70 kV / cm electric field for polarization treatment for 50-70 seconds.

Citation Information

Patent Citations

  • High-electrostriction sodium-bismuth-titanate-base lead-free piezoelectric material and preparation method thereof

    CN102633503A

  • Preparation method of sodium bismuth titanate-lead titanate piezoelectric monocrystal

    CN102817068A

  • Bismuth-containing piezoelectric material with piezoelectric reinforced structure and preparation method thereof

    CN104446451A

  • Samarium-doped sodium bismuth titanate-bismuth strontium titanate ceramic material with high energy storage density and preparation method thereof

    CN113213919A

  • Lead-free ferroelectric / electrostrictive ceramic material

    WO2006060191A2